Предмет: Алгебра,
автор: Неуловимыйтип
Решите уравнение
Ответы
Автор ответа:
0
4(х²-х)²+9х²=9х-2
4(х²-х)²+9(х²-х)+2=0 пусть (х²-х)=t
4t²+9t+2=0
D=81-32=49=7²
t1=(-9+7)/8=-1/4 х²-х=-1/4 х²-х+1/4=0
t2=(-9-7)/8=-2 х²-х=-2 D=1-4*1/4=0 х1=х2=0,5
х²-х+2=0
D=1-2*4<0 корней нет
Ответ: х=0,5
4(х²-х)²+9(х²-х)+2=0 пусть (х²-х)=t
4t²+9t+2=0
D=81-32=49=7²
t1=(-9+7)/8=-1/4 х²-х=-1/4 х²-х+1/4=0
t2=(-9-7)/8=-2 х²-х=-2 D=1-4*1/4=0 х1=х2=0,5
х²-х+2=0
D=1-2*4<0 корней нет
Ответ: х=0,5
Автор ответа:
0
исправьте x=0.5
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Английский язык,
автор: dedded896
Предмет: Математика,
автор: aylinmustafazade32
Предмет: Математика,
автор: zelenukdarina5
Предмет: Литература,
автор: irina82kz